Pengaruh Terpaan Konten Life Tips Akun TikTok @niaghan Terhadap Motivasi Pengembangan Diri Remaja di Kota Denpasar. - Ramadhana, Berlian; Suryawati, I Gusti Agung Alit; Pradipta, Ade Devia; Damasemil, Calvin (E-Jurnal Medium, 2024)
TikTok is a trending social media among teenagers. Various content is uploaded on TikTok. Such as life tips on TikTok account @niaghan regarding social life suggestions that can improve social and mental self-development. To see How exposure to life tips content from TikTok account @niaghan affects self-development, this study aims to determine the effect of exposure to content life tips from TikTok account @niaghan on motivation for self-development of adolescents in Denpasar City. This study uses a quantitative explanatory method using the Uses and Effect Theory and McClelland's Theory of Motivation. The findings of this study indicate that there is an influence of exposure to the content of life tips from TikTok @niaghan account on motivation for self-development of adolescents in Denpasar City, indicated by an R Square value of 0.69 which has a positive and significant value, and a correlation coefficient which has very strong relationship level. 0.830.   Keywords : Content life tips @niaghan, Self-development motivation, Social media exposure,  TikTok